Effect of Foliar Application of Nano-NPK Fertilizer on Growth and Yield of Broad bean (Vicia Faba L.) - Bayan Rokan Aziz; Dilzar Basit Zrar (Zanco Journal of Pure and Applied Sciences, 2021)
A field research was conducted during season 2019/2020 in Gradrasha field, collage of agricultural Engineering sciences at Salahaddin University, to evaluate the effect of foliar application of Nano- NPK fertilizer at different levels (0, 30, 60, 90 and 120 mg.l-1) for one and two times on growth and yield of (Vicia faba L.). The research was applied as foliar application of Nano-NPK at different levels (0, 30, 60, 90 and 120 mg.l-1). The results shows significant effect on most studied treatment. The results indicated that number of foliar application had significant influence on most vegetative, yield and yield component parameters, the best results were obtained from twice foliar application, the best values of number of branches.plant-1, chlorophyll content in leaves%, and dry matter of leaves (334.416, 5.381, 46.949 %, 22.789 % respectively) were obtained at the twice foliar application of Nano-NPK. However, the highest results of plant height, number of branches. plant-1, number of leaves. plant-1, leaves chlorophyll content %, dry matter in leaves and TSS in seed (131.448cm, 365.995, 6.120, 51.592%, 25.435ghighes and 16.107% respectively) were recorded from (120mg.l-1) of Nano- NPK. Moreover the foliar application of (120mg.l-1) Nano-NPK for two times gave highest significant effects on vegetative growth, yield and yield component.